Analysis of Learning Systems Perspective of Economic Learning Programs - Karolus Suban Waikelak; Imam Mukhlis; Hari Wahyono (CV. AFDIFAL MAJU BERKAH, 2023)
This research is motivated by the importance of learning programs as the first step made by schools, especially teachers to serve as guidelines in one school year. In addition, the learning program is also an important aspect of the learning system to be used as the basis for the implementation process and assessing learning outcomes. This study uses a qualitative approach with a type of phenomenology. The research was conducted at Santa Maria Catholic High School and Saint Albertus Catholic High School Malang. The informant collection technique in this study was a purposive sampling technique, namely class XI economics teachers. Data collection was carried out using interview, observation, and documentation techniques. The results of this study are economic learning programs in both schools including program planning as environmental input; and instrumental inputs such as determining Basic Competency (KD), Operational Verbs (KKO), content, and learning methods; preparation of learning tools; the availability of media and learning resources, as well as the establishment of an assessment program and Minimum Completeness Criteria (KKM), where teachers attend Work Meetings (Raker) and hold Study Field Teacher Consultations (MGBS) in planning, establishing, and compiling learning programs at the beginning of the school year. The purpose of this study is to describe economic learning programs that support the learning process and student learning outcomes as well as to be used as material for evaluating planning, determining and compiling next year's learning programs